TINGKAT KEMANDIRIAN PETANI KARET POLA SWADAYA DALAM PENGAMBILAN KEPUTUSAN USAHATANI DI DESA KUNTU KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Gunawan ' Sinaga; Roza ' Yulida; Kausar ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims : 1) to know the characteristics of the internal factors and external factors, 2)the level of independence the farmers, 3)analyzes the relationship characteristics of internal factors and external factors to the independence of the farmers. The determination of the location is purposive on the consideration in village many rubber farmers with the patterns of non-governmental organizations. Fetch method respondents by purposive sampling with the conditions in the village there is counseling activities and farmer groups active. Total respondents 60 farmers. Analysis of the data using descriptive method. The purpose of the first and the second analyzed with Likert scale, while the the third analyzed with rank Spearman correlation. Characterized internal factors : age (37- 55 years), formal education (finished elementary and high school), informal education (3 times in the last three years the number of members of the family (4), experience (19-35 years), tenure (17.801 - 35.400 m²),  motivation a low level of kekosmopolitan (0-196 km), revenue (Rp 3.010.000 - 5800.000), and characteristics external factors farmers: support farmer groups, counseling institutions, government policies and the role of community leaders category of "good" but the availability of infrastructure and production financial institutions and the source information the category of "low". The level independence organizations of pattern rubber farmers in decision-making and aquaculture, and harvest "high". Decision-making the infrastructure and production and marketing "low". The relationship characteristics external factors and is not related to the internal factors. Key Words: Internal Factors, external factors, the level of independence, and rubber farmers.